Weed Control for Ornamentals Inside Greenhouses and Other Enclosed Structures - Chris Marble; Jeremy Pickens (EDIS)
Maintaining a weed-free greenhouse is important for producing healthy and marketable crops. Weeds will compete with crops for water, light, and nutrients. Weeds can find favorable conditions for growth in gravel and along edges, tears, and worn areas of ground cloth. It is important to frequently scout for weeds. This 5-page fact sheet describes both chemical methods of controlling weeds, but also non-chemical methods, such as sanitation and prevention, hand weeding, and cultural control practices. Written by Chris Marble and Jeremy Pickens, and published by the Environmental Horticulture Department, November 2015.